Deciphering the combined effect of bone morphogenetic protein 6 and calcium phosphate on bone formation capacity of periosteum derived cells-based tissue engineering constructs. (15th October 2018) - Ji, Wei; Kerckhofs, Greet; Geeroms, Carla; Marechal, Marina; Geris, Liesbet; Luyten, Frank P.
Graphical abstract: Abstract: Cell based combination products with growth factors on optimal carriers represent a promising tissue engineering strategy to treat large bone defects. In this concept, bone morphogenetic protein (BMP) and calcium phosphate (CaP)-based scaffolds can act as potent components of the constructs to steer stem cell specification, differentiation and initiate subsequent in vivo bone formation. However, limited insight into BMP dosage and the cross-talk between BMP and CaP materials, hampers the optimization of in vivo bone formation and subsequent clinical translation. Herein, we combined human periosteum derived progenitor cells with different doses of BMP6 and with three types of clinical grade CaP-scaffolds (ChronOs®, ReproBone™, & CopiOs®). Comprehensive cellular and molecular analysis was performed based on in vitro cell metabolic activity and signaling pathway activation, as well as in vivo ectopic bone forming capacity after 2 weeks and 5 weeks in nude mice. Our data showed that cells seeded on CaP scaffolds with an intermediate Ca 2+ release rate combined with low or medium dosage of BMP6 demonstrated a robust new bone formation after 5 weeks, which was contributed by both donor and host cells. This phenomenon might be due to the delicate balance between Ca 2+ and BMP pathways, allowing an appropriate activation of the canonical BMP signaling pathway that is required for in vivo bone formation. For high BMP6 dosage, we found that the BMP6 dosage overrides the effect of the Ca 2+ release rate and this appeared to be a dominant factor for ectopic bone formation. Taken together, this study illustrates the importance of matching BMP dosage and CaP properties to allow an appropriate activation of canonical BMP signaling that is crucial for in vivo bone formation. It also provides insightful knowledge with regard to clinical translation of cell-based constructs for bone regeneration. Statement of Significance: The combination of bone morphogenetic proteins (BMP) and calcium phosphate (CaP)-based biomaterials with mesenchymal stromal cells represents a promising therapeutic strategy to treat large bone defects, an unmet medical need. However, there is limited insight into the optimization of these combination products, which hampers subsequent successful clinical translation. Our data reveal a delicate balance between Ca 2+ and BMP pathways, allowing an appropriate activation of canonical BMP signaling required for in vivo bone formation. Our findings illustrate the importance of matching BMP dosage and CaP properties in the development of cell-based constructs for bone regeneration.